Efficacy and Safety of TACE Combined With Sorafenib Plus Immune Checkpoint Inhibitors for the Treatment of Intermediate and Advanced TACE-Refractory Hepatocellular Carcinoma: A Retrospective Study - Zheng, Liyun; Fang, Shiji; Wu, Fazong; Chen, Weiqian; Chen, Minjiang; Weng, Qiaoyou; Wu, Xulu; Song, Jingjing; Zhao, Zhongwei; Ji, Jiansong (Frontiers in Molecular Biosciences, 2021)
Purpose The study aims to retrospectively investigate the efficacy and safety of sorafenib combined with transarterial chemoembolization (TACE) (TACE+Sor) vs. TACE combined with sorafenib plus immune checkpoint inhibitors (TACE+Sor+ICIs) in treating intermediate and advanced TACE-refractory hepatocellular carcinoma (HCC). Materials and Methods This study was approved by the ethics committee of Lisui Hospital, Zhejiang University, China. From January 2016 to June 2020, 51 eligible patients with intermediate or advanced TACE-refractory HCC received TACE+Sor (n=29) or TACE+Sor+ICIs (n=22). The differences in tumor response, adverse events (AEs), progression-free survival (PFS), and overall survival (OS) were compared between the two groups. Factors affecting PFS and OS were determined by Cox regression. Results The disease control rate was higher in the TACE+Sor+ICIs group than in the TACE+Sor group (81.82% vs 55.17%, P=0.046). Compared with the TACE+Sor group, PFS and OS were prolonged in the TACE+Sor+ICIs group (median PFS: 16.26 vs 7.30 months, P<0.001; median OS: 23.3 vs 13.8 months, P=0.012). Multivariate analysis showed that BCLC stage, alpha-fetoprotein and treatment were independent factors of PFS; BCLC, Child-Pugh class, ablation after disease progression and treatment were independent predictive factors of OS. Four patients in the TACE+Sor+ICIs group and three patients in the TACE+Sor group suffered from dose reduction or interruption (18.18% vs 10.34%, P=0.421). The incidence of ICI-related AEs in the TACE+Sor+ICIs group was well controlled.Conclusion The therapeutic schedule of TACE+Sor+ICIs demonstrated efficacy and safety in intermediate and advanced TACE-refractory HCC.